Characterization of a novel AICARFT inhibitor which potently elevates ZMP and has anti-tumor activity in murine models. Issue 1 (December 2018) - Brooks, Harold; Meier, Timothy; Geeganage, Sandaruwan; Fales, Kevin; Thrasher, Kenneth; Konicek, Susan; Spencer, Charles; Thibodeaux, Stefan; Foreman, Robert; Hui, Yu-Hua; Roth, Kenneth; Qian, Yue-Wei; et al.
Abstract AICARFT is a folate dependent catalytic site within the ATIC gene, part of the purine biosynthetic pathway, a pathway frequently upregulated in cancers. LSN3213128 is a potent (16 nM) anti-folate inhibitor of AICARFT and selective relative to TS, SHMT1, MTHFD1, MTHFD2 and MTHFD2L. Increases in ZMP, accompanied by activation of AMPK and cell growth inhibition, were observed with treatment of LY3213128. These effects on ZMP and proliferation were dependent on folate levels. In human breast MDA-MB-231met2 and lung NCI-H460 cell lines, growth inhibition was rescued by hypoxanthine, but not in the A9 murine cell line which is deficient in purine salvage. In athymic nude mice, LSN3213128 robustly elevates ZMP in MDA-MB-231met2, NCI-H460 and A9 tumors in a time and dose dependent manner. Significant tumor growth inhibition in human breast MDA-MB231met2 and lung NCI-H460 xenografts and in the syngeneic A9 tumor model were observed with oral administration of LSN3213128. Strikingly, AMPK appeared activated within the tumors and did not change even at high levels of intratumoral ZMP after weeks of dosing. These results support the evaluation of LSN3213128 as an antineoplastic agent.